Orthodontic Treatment Needs Among Population Visiting the Liaquat University of Medical & Health Sciences Hospital (Medical Forum Monthly, 2024)
ABSTRACTObjective: This study was to determine the orthodontic treatment need in local population visiting the Liaquat University of Medical & Health Sciences Hospital by using index of orthodontic treatment need.Study Design: Descriptive cross sectional studyPlace and Duration of Study: This study was conducted on patients visiting to Dental outpatient department (OPD) of Liaquat University of Medical & Health Sciences Hospital, Jamshoro from September 2012 to October 2013.Materials and Methods: Informed written consent was taken from 150 patients’ satisfying the inclusion criteria, history and clinical examination was done on patients by using index of orthodontic treatment need. SPSS version 19 was used to analyze the data and frequency was determined for categorical variables. Mean and standard deviation was computed for numerical variables.Results: According to Dental Health Component (DHC) treatment need 36.7%, 34.7%, 24.7% and 4.0% found to have orthodontic treatment need from no little treatment to very great treatment respectively and according to Aesthetic Component (AC) treatment need 49.3%, 44.0% and 6.7% found to have orthodontic treatment need from no little treatment to great treatment need.Conclusion: It was concluded that the patients of this locality found to have increased need for orthodontic treatment.